Uma estrutura conceitual para a aplicação do postponement : estudo multicaso em empresas da indústria de alimentos - Ferreira, Karine Araújo (Universidade Federal de São Carlos, 2009)
The postponement strategy is more and more used by companies with the increasing complexity and variety of products, currently required by the market. In essence, the postponement is used to delay as much as possible the final configuration and/or movement of products and services, until the demand known. In recent years, this subject has attracted attention of scholars and executives in the several countries. Despite the increasing attention to the subject, little is known about is implementation, especially in the Brazilian food industry. Thus, this research attempt to investigate the adoption of the postponement strategy in companies of this sector. The literature review has covered the last 59 years of study on the subject, which resulted in the development of a general conceptual framework for implementing the postponement strategy. In the order to adopt this structure to the food industry, were developed six exploratory case studies in orange juice and fruits processing companies, and tree of them that have a main activity processing of orange juice and other three, the production of tomatoes. In addition to further discussion on the issue and verification of its application in food companies, this works presents two main contributions. The first is to present a general conceptual framework for implementation of postponement, which can and should be suitable for different industry sectors. The second is the adequacy of this conceptual framework for using in food companies, specifically orange juice and fruits processing companies, and the presentation of information that provide subsidies for adoption, consolidation and evaluation of postponement in the companies.
Keywords: Engenharia de produção; Postergação; Customização; Estratégia de operações; Indústria alimentar; Empresas produtoras de sucos e conservas de frutas; ENGENHARIAS::ENGENHARIA DE PRODUCAO